Constructing Students' Fiqh Understanding through Learning Preferences and Teaching Methods in a Pesantren-Based Madrasah Aliyah - Baikal Al Qofidh; Ahmad Sulton; Nur Kolis (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study looks at how students build their understanding of Fiqh through learning preferences, teaching methods, and pesantren-based religious culture at MA Ma'arif Nahdlatul Ummah Jarakan Banyudono Ponorogo during the 2025/2026 academic year. The starting problem is a familiar one in Islamic education: Fiqh tends to get taught as a body of legal concepts to memorize, when students also need interpretive judgment, religious disposition, and the practical skill to carry out worship and social conduct correctly. Drawing on Bloom's cognitive taxonomy, comprehension here means the ability to interpret information, restate concepts in one's own words, and connect that knowledge to specific situations students actually face. Interactive lecture, question-and-answer, discussion, demonstration, practice, and problem-solving each played a part in helping students link legal concepts to religious procedure and to the contextual decisions they encounter outside the classroom. Pesantren culture, particularly students' earlier exposure to Fiqh material, their habituated worship practice, and participation in Bahtsul Masa'il, reinforced their reasoning, their carefulness, and their day-to-day religious awareness. The study's central point is that a practical grasp of Fiqh grows out of the interaction between classroom instruction, how students choose to engage with material, and the religious life they already live inside the pesantren.